A refugee pattern language – Rpl 9: Design and construction for refugees - Chaiwat Pamanee; Neis Hans Joachim (Lodz University of Technology Press, 2023)
This paper presents chapter 9 of a larger project ‘Refugee Pattern Language’. Employing Pattern Language method, the research is based on field work, case studies, and literature. We propose nine patterns of design and construction for refugees in a concise format. They address design approach, fabrication, and building construction along with factors related to building agencies, construction skills, and building materials. Here, we encourage the use of the principle of participation at multiple levels in the design, building, and planning process. Accommodating the needs of these influx migrants is a humanitarian responsibility that gives opportunities for redevelopment which also benefits vulnerable populations in the time of global refugee crisis. Individuals, professionals, NGOs, and governments can adopt these patterns to offer pragmatic humanistic solutions for different scenarios and scales of refugeereceiving sites.
Keywords: pattern language; refugee; housing; building; construction; język wzorcowy; uchodźca; mieszkalnictwo; budynek; budownictwo